2010
DOI: 10.4293/108680810x12785289144395
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Common Bile Duct Exploration in Patients With Gallstones and Choledocholithiasis

Abstract: Failed ERCP appears to decrease the success rate of a laparoscopic approach for common bile duct exploration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 21 publications
(18 reference statements)
2
14
0
1
Order By: Relevance
“…There were no retained stones in the two previous reports or the present study, thus supporting entirely opening the cystic duct to avoid retained stones . Previous studies have considered patients with unsuccessful preoperative EST for BDS to be complex cases , and these assessments are consistent with this study. In the present study, 13% of patients with unsuccessful preoperative EST had complications, whereas 12% without preoperative EST had complications.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…There were no retained stones in the two previous reports or the present study, thus supporting entirely opening the cystic duct to avoid retained stones . Previous studies have considered patients with unsuccessful preoperative EST for BDS to be complex cases , and these assessments are consistent with this study. In the present study, 13% of patients with unsuccessful preoperative EST had complications, whereas 12% without preoperative EST had complications.…”
Section: Discussionsupporting
confidence: 90%
“…Complication rates for laparoscopic choledochotomy have been reported to be between 1.2% and 18% for the transcystic approach and between 7% and 18.74% for the direct choledochotomy approach . The incidence of complications among those with unsuccessful preoperative EST in our study was similar to the incidence in these reports . This study demonstrated that the incidence of complications among those with unsuccessful preoperative EST was not significantly higher than among those without the unsuccessful EST.…”
Section: Discussionsupporting
confidence: 84%
“…In these cases the use of methods to achieve stone fragmentation increases the effectiveness of LCBDE. 1,2 The first experience using laser lithotripsy for the treatment of bile duct stones is attributed to Orii et al 12 in 1983, who reported 8 patients with intrahepatic stones and 3 patients with choledocholithiasis treated with an yttriumaluminum-garnet laser. The procedure was performed shortly after the ineffectiveness of the endoscopic treatment was shown.…”
Section: Discussionmentioning
confidence: 99%
“…In patients in whom ERCP is ineffective, the laparoscopic conversion rate increases mainly because of impacted stones that require complex management. 2 The incorporation of new technologies such as robotic surgery and a holmium laser in the management of choledocholithiasis increases the success rate, allowing proper handling of complex cases. 3,4 Robot-assisted surgery helps to overcome difficulties of other minimally invasive approaches, providing a 3-dimensional view and high maneuverability of the instruments.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore the treatment can be challenging because of the anatomical changes due to the bariatric procedure. 1,2 Diverse kinds of protocols exist: prophylactic surgery (simultaneous cholecystectomy and gastric bypass in every patients, whether they have or not cholelithiasis), 3,4 elective (simultaneous cholecystectomy with conventional gastric bypass in the patients with asymptomatic cholelithiasis), [5][6][7] and conventional cholecystectomy only in the presence of cholelithiasis with symptoms. [8][9][10][11] The incidence of cholelithiasis post gastric bypass is estimated around 37%.…”
mentioning
confidence: 99%